Relationship between dry-land upper-limb power and underwater stroke power using medicine ball overhead slam as a predictor of swimming speed by upper limbs only - Ikeda, Y.; Nara, R.; Baba, Y.; Yamashiro, S.; Hisamitsu, T.; Shimoyama, Y. (Scientific Journal of Sport and Performance, 2022)
The relationship between power output underwater and on land was investigated by evaluation of underwater power output by the back and upper limbs. Thirteen male competitive swimmers performed the one underwater arm stroke (OUAS) trial, medicine ball overhead slam (MBOS) trial, and lat pull-down test as a predictor of back and upper-limb strength and power underwater and on land. The maximum horizontal velocity of the greater trochanter in OUAS correlated with all vertical velocities of the MB at release in MBOS (r = 0.544 - 0.777), with 5 repetition maximums in the lat pull-down test (r = 0.555 - 0.729), and with FINA points (r = 0.783). In the OUAS trial, increases in horizontal velocity from the start of the OUAS to the maximum horizontal velocity correlated with horizontal velocity at the start of trial, and high-level swimmers accelerated their body in a manner that was dependent on horizontal velocity at the start of the OUAS. These results suggest that underwater power output using only the upper limbs is closely associated with power and strength in dry-land exercise, and that back and upper-limb power and strength are crucial physical elements for competitive swimmers.